Leptospirosis Ditinjau dari Aspek Mikrobiologi - Ika Ningsih; Mardiastuti H Wahid (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2022)
Leptospirosis is an acute infectious disease in humans caused by Leptospira sp. This disease is classified as a zoonosis that usually occurs during the flood and is commonly transmitted through rat urine. Leptospirosis occurs through humans contact with animals or the environment that have been contaminated by Leptospira. There are wide spectrum clinical manifestations of leptospirosis varying from self-limited to severe disease. Leptospira commonly enters human body through conjunctiva or injured skin, food or beverage contaminated with urine’s rat containing Leptospira. This disease is very difficult to be distinguished from other diseases such as meningitis, malaria, dengue fever, hepatitis and enteric fever. Clinical symptoms of leptospirosis are nonspecific and due to the difficulties in conforming the diagnosis so that resulted to the misdiagnosis of this disease. Microbiological examination is done by Rapid Diagnostic Test, Microscopic Agglutination Test, Polymerase Chain Reaction test and others. Prevention can be done by inhibiting the entry of Leptospira to human body via implementing clean and healthy life and surrounding environment.